1982
DOI: 10.1111/j.1432-1033.1982.tb06787.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Inactivation by 13‐Hydroperoxylinoleic Acid and Lipohydroperoxidase Activity of the Reticulocyte Lipoxygenase

Abstract: 1. The self-inactivation of lipoxygenase from rabbit reticulocytes with linoleic acid at 37 "C is caused by the product 13-hydroperoxylinoleic acid. This inactivation is promoted by either oxygen or linoleic acid.2. Lipohydroperoxidase activity was demonstrated with 13-hydroperoxylinoleic acid plus linoleic acid as hydrogen donor under anaerobic conditions at 2 "C. The products were 13-hydroxylinoleic acid, oxodienes and compounds of non-diene structure similar to those produced by soybean lipoxygenase-I .3. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 21 publications
2
8
0
1
Order By: Relevance
“…A similar oxygen dependence of the LOX activation was recently reported for ALOXE3 [130]. Rabbit ALOX15 undergoes suicidal inactivation during the oxygenation of polyenoic fatty acids [39]. Initially, it has been suggested that the hydroperoxy fatty acids formed may oxidize catalytically relevant amino acids at the active site.…”
Section: Monooxygenation Of Free Fatty Acidsmentioning
confidence: 67%
See 3 more Smart Citations
“…A similar oxygen dependence of the LOX activation was recently reported for ALOXE3 [130]. Rabbit ALOX15 undergoes suicidal inactivation during the oxygenation of polyenoic fatty acids [39]. Initially, it has been suggested that the hydroperoxy fatty acids formed may oxidize catalytically relevant amino acids at the active site.…”
Section: Monooxygenation Of Free Fatty Acidsmentioning
confidence: 67%
“…A lipohydroperoxidase activity has also been described for rabALOX15 [39,151]. As for humALOXE3 this catalytic activity was not restricted to anaerobic conditions, but also occurs when oxygen is present [152,153].…”
Section: Lipohydroperoxidase Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…However, for the activation only the occurrence of a hydroperoxy group is required, whereas the steric structure does not appear to be of importance. On the other hand, a high cellular level of hydroperoxy fatty acids may inactivate both lipoxygenase and cyclooxygenase (44,45). A steady state of hydroperoxide-generating and hydroperoxide-consuming processes seems to be important for the autoregulation of the lipoxygenase and cyclooxygenase pathways.…”
Section: The Possible Biological Importance Of Primary Lipoxygenamentioning
confidence: 99%